Introduction to environmental engineering - Davis, Mackenzie Leo, 1941-; Cornwell, David A., 1948- (McGraw-Hill, 2013)
Contains the fundamental science and engineering principles needed for introductory courses and used as the basis for advanced courses in environmental engineering. This title applies the concepts of sustainability and materials and energy balance as a means of understanding and solving environmental engineering issues.